Professores em luta: o Sindicalismo Docente sob a ótica da Imprensa Paranaense (1947-1964) - Dezan, Darlon (2020)
The main purpose of this dissertation is to analyze the way in which the Paraná press, between the years 1947 to 1964, publicized the actions of the teachers of the public and private network in Paraná, as an organization of the working class. Through the portal of the Hemeroteca Digital, linked to the National Library, news from three Paraná newspapers was selected: O Dia, Correio do Paraná and Diário da Tarde. Supported by the periodic sources and the bibliography, the analyzes were based on the observation of power relations, having as a central theoretical framework historical and dialectical materialism, mainly in the examination of the relations and conflicts inherent to the State, the Economy and Education. For the study of the materials conveyed by the researched periodicals, he also used the concepts expressed by Bakhtin and his interpreters, as is the case with dialogue, which greatly help in understanding the relationship between language and society. In turn, the spatial approach was based on the case of Paraná, with the period between the end of the Estado Novo and the civil-military pre-coup of 1964 as its time frame. This academic research had as its primary focus not only the analysis of the discourse produced about teachers in struggle, but also the proposition of a narrative from this period in the history of education in Paraná. Consequently, the aim was to contribute to this study to reflect on the construction of an image of the teacher in the social imaginary of Paraná.